Towards a Theory of Network Facilitation: A Microfoundations Perspective on the Antecedents, Practices and Outcomes of Network Facilitation - Elisabeth F. Mueller (British Journal of Management, 2021)
Firms cooperate in inter-firm networks to foster their competitiveness and improve their innovation outcomes. In many cases, network facilitators who are either embedded in a lead firm or a third-party organization manage the cooperation among the network firms. This qualitative study adopts a microfoundations perspective to investigate the behavioural antecedents of the network facilitators, their facilitation practices and the related network-level outcomes. Results show that lead-firm facilitators more strongly invest in trust-building measures since they are considered deficient in benevolence and integrity. Without these investments, they run the risk that conflicts of interest hinder the stimulation of positive network-level outcomes. Third-party facilitators, by contrast, enjoy certain credits of trust and focus on balancing firm interests from the network's activation, but need to invest in enhancing their competencies and skills with regard to the industry the firms operate in. The findings contribute to developing a theory of network facilitation by providing a nuanced understanding of how network-level outcomes can be reduced to individual-level factors.
Keywords: 650